Photochemical Co-Oxidation of Sulfides and Phosphines with Tris(p-bromophenyl)amine. A Mechanistic Study - Bonesi, Sergio Mauricio (2018)
The photochemistry of tris(p-bromophenyl)amine was investigated in a nitrogen- and oxygen-flushed solution under laser flash photolysis conditions. The detected intermediates were the corresponding amine radical cation ("Magic Blue") and the N-phenyl-4a,4b-dihydrocarbazole radical cation that, under an oxygen atmosphere, is converted to the corresponding hydroperoxyl radical. The role of the last species was supported by the smooth co-oxidation of sulfides to sulfoxides. On the other hand, co-oxidation of nucleophilic triarylphosphines to triarylphosphine oxides arose from an electron transfer between the photogenerated "Magic Blue" and phosphine that prevented the amine cyclization. In this case, intermediate Ar3POO•+ was found to play a key role in phosphine oxide formation.